(untitled) - Valacich, Joseph S. (Upper Saddle River, N.J., 2009)
This text addresses how to organize and access information strategically, how to work as part of a team, and how to use the Internet effectively. The three authors draw on their many years of teaching experience to present the skills and techniques that systems analysts need to create information systems for businesses. They cover the foundations of systems development and then outline each stage of planning and selection, analysis, design, and implementation and operation
Keywords: System design,System analysis,Phân tích hệ thống,Thiết kế hệ thống